Analisis Kecelakaan Kerja pada Pekerja Tambang Batubara : LITERATURE REVIEW - Dyah Tri Permatasari; Yuliani Setyaningsih; Daru Lestantyo (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Through accident analysis, we can design effective measures to prevent accidents. Therefore, this study aims to analyze occupational accidents in coal mining workers. This study adopted a literature study approach, in which the data search process was carried out systematically referring to the PRISMA guidelines. Information retrieval encompasses not only the use of keywords but also Boolean operators in order to enhance the results of the search: “coal” AND “mining” AND “workers” AND “workplace accident”, Inclusion criteria of the articles were those published between the years 2019 to 2024. This study identified that the risk of accidents in coal mining is mainly caused by physical hazards such as roof collapse, fire, and gas explosion, as well as exposure to hazardous chemicals. In addition, human factors such as lack of safety awareness and weaknesses in management systems also contribute significantly to the high accident rate. The results show that the risk of accidents in coal mining is caused by physical hazards such as roof collapse, fire, gas explosion and chemical hazards such as toxic gases as well as human factors. These findings therefore underline the need for comprehensive measures that would improve occupational safety in coal mines. This will include improved safety management systems, more awareness of the workers themselves, and better regulation of physical hazards. These measures consequently offer protection not only to the employees but also present tokens of the organization towards being socially and ecologically responsible. Keywords: Coal, Mining, Workers, Workplace Accidents.